A single-manufacturer multi-retailer sustainable reworking model for green and environmental sensitive demand under discrete ordering cost reduction. Issue 1 (2nd January 2023) - Malleeswaran, B.; Uthayakumar, R.
Abstract : This paper develops an economic production quantity (EPQ) model for a single-manufacturer multi-retailer (SMMR) production and reworking system with green and environmental sensitive customer demand. The minimum cost of the manufacturer has obtained under carbon emissions (CE) policies and discrete ordering cost reduction. The model is used to optimize the total number of shipments, greening investment level, environmental measure, and lot size for productions and rework. This research work determines that the manufacturer's and retailer's profits will be increased after considering the environmental and green dependent demand of customers. Further, the development of green and environmental demand is proposed to minimize the CE and maximize the demand for the customers. In the existing literature, no discrete investment is developed for reducing the cost of ordering for the retailer/buyer. However, in this paper, we have introduced it. We provide numerical examples to explain the models and determine the significance of model parameters.